A duplicated copy of id2b is an unusual sex-determining candidate gene on the Y chromosome of arapaima (Arapaima gigas) - Adolfi, Mateus C.; Du, Kang; Kneitz, Susanne; Cabau, Cédric; Zahm, Margot; Klopp, Christophe; Feron, Romain; Paixão, Rômulo V.; Varela, Eduardo S.; de Almeida, Fernanda L.; de Oliveira, Marcos A. [UNESP]; Nóbrega, Rafael H. [UNESP]; et al. (Springer Nature, 2021)
Arapaima gigas is one of the largest freshwater fish species of high ecological and economic importance. Overfishing and habitat destruction are severe threats to the remaining wild populations. By incorporating a chromosomal Hi-C contact map, we improved the arapaima genome assembly to chromosome-level, revealing an unexpected high degree of chromosome rearrangements during evolution of the bonytongues (Osteoglossiformes). Combining this new assembly with pool-sequencing of male and female genomes, we identified id2bbY, a duplicated copy of the inhibitor of DNA binding 2b (id2b) gene on the Y chromosome as candidate male sex-determining gene. A PCR-test for id2bbY was developed, demonstrating that this gene is a reliable male-specific marker for genotyping. Expression analyses showed that this gene is expressed in juvenile male gonads. Its paralog, id2ba, exhibits a male-biased expression in immature gonads. Transcriptome analyses and protein structure predictions confirm id2bbY as a prime candidate for the master sex-determiner. Acting through the TGFβ signaling pathway, id2bbY from arapaima would provide the first evidence for a link of this family of transcriptional regulators to sex determination. Our study broadens our current understanding about the evolution of sex determination genetic networks and provide a tool for improving arapaima aquaculture for commercial and conservation purposes.